Cancer‐causing MAP2K1 mutation in a mosaic patient with cardio‐facio‐cutaneous syndrome and immunodeficiency. Issue 12 (12th September 2022) - Zakharova, Victorya; Raykina, Elena; Mersiyanova, Irina; Deordieva, Ekaterina; Pershin, Dmitry; Vedmedskia, Victorya; Rodina, Yulia; Kuzmenko, Natalia; Maschan, Michael; Shcherbina, Anna
Abstract: RASopathies are disorders caused by germline mutations in genes that encode components of the RAS/mitogen‐activated protein kinase (MAPK) pathway. These syndromes share features of developmental delay, facial dysmorphisms, and defects in various organs, as well as cancer predisposition. Somatic mutations of the same pathway are one of the primary causes of cancer. It is thought that germline cancer‐causing mutations would be embryonic lethal, as a more severe phenotype was shown in Drosophila and zebrafish embryos with cancer MAP2K1 mutations than in those with RASopathy mutations. Here we report the case of a patient with RASopathy caused by a cancer‐associated MAP2K1 p.Phe53Leu mutation. The postzygotic mosaic nature of this mutation could explain the patient's survival.